2022
DOI: 10.1097/pec.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Pediatric Mental and Behavioral Health Visits to the Emergency Department

Abstract: ObjectivesThis study aimed to describe changes in pediatric emergency department (ED) mental and behavioral health (MBH) visits before and during the early COVID-19 pandemic.MethodsWe retrospectively reviewed medical records of patients aged from 5 to 17 years presenting to the pediatric ED of a major tertiary care hospital with MBH-related concerns from March 2017 to September 2020. We evaluated trends in MBH ED visits over the study period, specifically comparing patient demographics, diagnosis categories, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This is in line with the decreased number of pediatric ED visits across the U.S. during the pandemic (17). Despite overall declines in ED visits, we found that the percentage of ED visits for chest pain increased during the pandemic, similar to findings that ED visits for certain types of injuries (e.g., drug poisonings, self-harm, and firearm injuries) and mental health complaints increased during the pandemic (17,18). A large retrospective study did not find differences in the relative proportion of pediatric ED visits for chest pain during the pandemic, however, the study was limited to the first year of the pandemic (19).…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with the decreased number of pediatric ED visits across the U.S. during the pandemic (17). Despite overall declines in ED visits, we found that the percentage of ED visits for chest pain increased during the pandemic, similar to findings that ED visits for certain types of injuries (e.g., drug poisonings, self-harm, and firearm injuries) and mental health complaints increased during the pandemic (17,18). A large retrospective study did not find differences in the relative proportion of pediatric ED visits for chest pain during the pandemic, however, the study was limited to the first year of the pandemic (19).…”
Section: Discussionsupporting
confidence: 83%
“…An increase in admissions has been also recorded, affecting adolescents with suicidality/self-harm and substance-related disorders [ 6 ]. Importantly, 78.2% of adolescent admissions were due to suicidal behavior associated with family risk factors and life stressors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%